PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, DAN PASAR TERHADAP HARGA SAHAM PADA PERUSAHAAN PARIWISATA, HOTEL, DAN RESTO YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Alethia Veritas Nico Artanto; Rahman Amrullah Suwaidi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The tourism industry is making good profits and also has good fundamentals. However, inthe previous year it had decreased. However, the performance of stock prices is not directlyproportional to the achievement of profits. This study aims to determine the effect ofprofitability ratios, liquidity ratios, and market ratios on stock prices in tourism, hotel andrestaurant companies listed on the Indonesia Stock Exchange. The population in this studyare tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange(IDX) as many as 20 companies. The sampling technique used is purposive samplingtechnique in order to obtain a sample of 13 companies based on predetermined criteria.The data analysis method used is multiple linear regression. Based on the results of thestudy indicate that profitability and liquidity do not contribute to changes in stock prices intourism companies, hotels, and restaurants listed on the Indonesia Stock Exchange (IDX).Meanwhile, the market ratio contributed to changes in the stock prices of tourism, hoteland restaurant companies listed on the Indonesia Stock Exchange for the 2016 – 2019period.